Infestation of fruit fly, Bactrocera (Diptera: Tephritidae) on mango (Mangifera indica L.) in peninsular Malaysia - Mohamed, Salmah; Adam, Nur Azura; Muhamad Awang, Rita; Lau, Wei Hong; Ahmad, Hamdan (Faculty of Science and Technology, University of El Oued, 2017)
A survey was carried out in mango orchards in Peninsular Malaysia with aimed to determine the infestation levels of fruit fly Bactrocera (Diptera: Tephritidae) on mango (Mangifera indica L.) through damaged fruit collection. Two fruit fly species emerged from the collected fruits: Bactrocera dorsalis (Hendel) and Bactrocera carambolae (Drew & Hancock). Bactrocera dorsalis was recorded the most abundant species (91%) compared to B. carambolae (9%). The highest fruit infestation was observed in Bumbong Lima (93.49±2.25 pupae/kg), followed by Bukit Changgang (36.08±8.35 pupae/kg) and Pulau Gadong (26.78 ±4.86 pupae/kg) whilst Jitra showed the lowest fruit infestation (10.79±3.34 pupae/kg).